Studies in religion : a comparative approach to theological and philosophical themes - Richards, Glyn (St. Martin's Press, 1995)
These studies in religion look at Hindu, Buddhist and Christian themes and examine the spiritual insights and philosophical reflections of thinkers from different religious traditions. Where appropriate comparisons are drawn between the views of representatives of the different traditions from an empathetic standpoint and in a way that would meet with the approval of adherents of those religions. The main aim of these essays is to try and enable us to escape from the small island of our own cultural tradition and to explore the diversity of other cultures with their variety of religious experiences.